2018
DOI: 10.1101/420315
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predicting evolution using frequency-dependent selection in bacterial populations

Abstract: Predicting how pathogen populations will change over time is challenging. Such has been the case with Streptococcus pneumoniae, an important human pathogen, and the pneumococcal conjugate vaccines (PCVs), which target only a fraction of the strains in the population. Here, we use the frequencies of accessory genes to predict changes in the pneumococcal population after vaccination, hypothesizing that these frequencies reflect negative frequency-dependent selection (NFDS) on the gene products. We find that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Preservation of gene frequencies in the population through negative frequency-dependent selection has been shown to exist in pneumococci, and can be used to predict serotype replacement in carriage [16,36]. This suggests that the gene content of a GPSCs influences whether it will undergo replacement or expansion after vaccine perturbation.…”
Section: Discussionmentioning
confidence: 99%
“…Preservation of gene frequencies in the population through negative frequency-dependent selection has been shown to exist in pneumococci, and can be used to predict serotype replacement in carriage [16,36]. This suggests that the gene content of a GPSCs influences whether it will undergo replacement or expansion after vaccine perturbation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has shown that models that incorporate genomics or clonal groups can forecast which serotypes will be successful after vaccination [19, 20, 31]. Future work could combine the results of this study with new genomics studies, directly incorporating information on the fitness of a serotype (e.g., as calculated by Azarian) in these models, or this type of model structure could be used to benchmark alternative modeling approaches.…”
Section: Discussionmentioning
confidence: 99%
“…However, when the goal is to examine emerging serotypes, it is important to consider individual serotypes. Recent work has used genomic data with models of negative frequency-dependent selection to quantify post-vaccine expansion patterns [19, 20]. However, whole genome sequence data are not always widely available, and their interpretation is complex.…”
mentioning
confidence: 99%
“…We then consider the response of repertoire structure as a manifestation of whether the influence of NFDS recovers quickly after the intervention. We end by drawing plausible analogies and implications for other ecological systems (Forrister et al, 2019a;Azarian et al, 2019), in particular for communities of species under stabilizing competition, Janzen-Connell mechanisms of coexistence and other forms of balancing selection.…”
Section: Introductionmentioning
confidence: 99%